Models for estimating the anthropometric dimensions using standing height for furniture design. Issue 3 (1st July 2014) - Ismaila, S.O.; Akanbi, O.G.; Ngassa, C.N.
Abstract : Purpose: – The purpose of this study was to obtain some anthropometric dimensions of students in secondary schools necessary for the design of school furniture and use them to establish the models that best determine the relationships among the anthropometric dimensions and standing height. Design/methodology/approach: – A total of 480 students aged 10 to 18 years ( n = 480, SD = ± 2.3 years) were randomly selected from eight public and eight private secondary schools in Ibadan, South West Nigeria. All the dimensions were subjected to curve estimation using Statistical Products and Services Solution 16.0 Statistical Package. The models with p < 0.005 and highest coefficient of determinations were selected as the best models to predict the relationships among the standing height and other variables. Findings: – The study proposes 11 models using standing height to estimate necessary anthropometric dimensions for the design of school furniture. The results of the study show that all anthropometric dimensions correlate more non-linearly with standing height than linearly. Originality/value: – The proposed models will have wide applications for the estimation of anthropometric data necessary for the design and construction of school furniture for use in secondary schools in South Western Nigeria.